2004
DOI: 10.1002/ijc.20298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exposure to light‐at‐night on life span and spontaneous carcinogenesis in female CBA mice

Abstract: The effect of constant illumination on the development of spontaneous tumors in female CBA mice was investigated. Fifty female CBA mice starting from the age of 2 months were kept under standard light/dark regimen (12 hr light: 12hr dark; LD) and 50 CBA mice of similar age were kept under constant illumination (24 hr a day, 2,500 Lux, LL). Exposure to the LL regimen decreased food consumption but did not influence body weight, significantly accelerated age-related disturbances in estrous function, and was foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 34 publications
0
39
0
1
Order By: Relevance
“…A possibility exists that exposure to continuous overnight illumination produced the observed estrous cycle disruption in the CMS group. However, while previous studies suggest that exposure to constant light lengthens or disrupts the estrous cycle in rodents (Fiske 1941;Maric et al 1965;Cvijić et al 1998), these changes have typically been reported following chronic periods (e.g., from 2 weeks to 3 months) of constant light situations (Ivanišević-Milovanovićc et al 1995;Anisimov et al 2004). In contrast, the brief periods of continuous illumination used in the current protocol (12 h, twice weekly) likely produced minimal, if any, direct effects on the estrous cycle in female rats.…”
Section: Discussionmentioning
confidence: 97%
“…A possibility exists that exposure to continuous overnight illumination produced the observed estrous cycle disruption in the CMS group. However, while previous studies suggest that exposure to constant light lengthens or disrupts the estrous cycle in rodents (Fiske 1941;Maric et al 1965;Cvijić et al 1998), these changes have typically been reported following chronic periods (e.g., from 2 weeks to 3 months) of constant light situations (Ivanišević-Milovanovićc et al 1995;Anisimov et al 2004). In contrast, the brief periods of continuous illumination used in the current protocol (12 h, twice weekly) likely produced minimal, if any, direct effects on the estrous cycle in female rats.…”
Section: Discussionmentioning
confidence: 97%
“…However, the experimental conditions of many of these animal studies were far from the reality of human shift workers. For example, some involved xenografts (addressing tumor growth rather than cancer initiation and/or progression) [4,5], chemically induced tumor models [6,7], or continuous bright light exposure, which can lead to suppression of circadian rhythmicity [8,9]. Here, we have exposed breast cancer-prone p53 R270Hª/+ WAPCre conditional mutant mice (in a FVB genetic background) to chronic CRD by subjecting them to a weekly alternating light-dark (LD) cycle throughout their life.…”
Section: Discussionmentioning
confidence: 99%
“…2А) достоверно различаются как у самцов, так и у самок (p < 0,001 по критерию Колмогорова-Смирно-ва). У самцов гетерозиготной по гипоморфной аллели гена dSir2 линии Sir2 17 /+, также как и у контрольной линии, в темноте происходило достоверное (p < 0,001) увеличе-ние МеПЖ (на 12 %), времени 90%-й гибели особей (на 17 %, p < 0,004), MRDT, а параметр α уравнения Гомпер-тца в темноте уменьшился на 22 % (p < 0,007 по критерию Хи-квадрат). У самок гетерозиготной линии Sir2 17 /+ в темноте наблюдалось незначительное снижение времени 90 %-гибели особей (на 5 %), MRDT, медиана не измени-лась, а значение параметра α увеличилось на 10 %.…”
Section: результатыunclassified